PERBANDINGAN MODEL DISCOVERY LEARNING DAN BLENDED LEARNING TERHADAP PENCAPAIAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS - Irfan Septiyan; Nurul Anriani; Aan Hendrayana (Universitas Sultan Ageng Tirtayasa, 2019)
The purpose of this study is to examine theachievement of mathematical problem solving abilitiesbetween students who obtain learning with the discoverylearning model and students who obtain learning with theblended learning model. This research is a mixed methodresearch with concurrent embedded method. This studyconsisted of two experimental groups who learned bydiscovery learning and blended learning models. Theresearch population is students in one of the junior highschools in Serang Regency. Banten with a class VIIIresearch sample. Data analysis was performedquantitatively and qualitatively. Quantitative analysis isused to calculate differences in the achievement ofstudents' mathematical problem solving abilities, whilequalitative data analysis is used to strengthen the resultsof quantitative analysis. The results showed thepercentage of achievement of students' mathematicalproblem solving abilities that obtained learning with thediscovery learning model with students who obtainedlearning with the blended learning model in the mediumcategory. There was no significant difference in theachievement of mathematical problem solving abilitiesbetween the two experimental groups.